2000
DOI: 10.1161/01.cir.102.20.2473
|View full text |Cite
|
Sign up to set email alerts
|

Mental Stress Induces Transient Endothelial Dysfunction in Humans

Abstract: Background —Mental stress has been linked to increased morbidity and mortality in coronary artery disease and to atherosclerosis progression. Experimental studies have suggested that damage to the endothelium may be an important mechanism. Methods and Results —Endothelial function was studied in 10 healthy men (aged 50.4±9.6 years) and in 8 non–insulin-dependent diabetic men (aged 52.0±7.2 years). Brachial artery flow-mediated dilation (FMD, endothelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
371
6
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(408 citation statements)
references
References 42 publications
18
371
6
13
Order By: Relevance
“…In the present study, endothelial function was reduced after night-shift work; this effect was alleviated by short-term lavender aromatherapy. A similar transient endothelial dysfunction was observed in association with several factors such as hyperglycemia, 22 hypertriglyceridemia, 23 mental stress 24 and smoking. 25 Such transient but frequent endothelial dysfunction potentially promotes the pathogenesis of early-stage atherosclerosis and the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, endothelial function was reduced after night-shift work; this effect was alleviated by short-term lavender aromatherapy. A similar transient endothelial dysfunction was observed in association with several factors such as hyperglycemia, 22 hypertriglyceridemia, 23 mental stress 24 and smoking. 25 Such transient but frequent endothelial dysfunction potentially promotes the pathogenesis of early-stage atherosclerosis and the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 68%
“…Endothelial dysfunction in obesity is partly due to diminished NO-availability (84), which may explain the reduced vasodilatory response not only to insulin but also to stress. A transient impaired endothelial function has also been reported after acute stress in healthy subjects (85).…”
Section: Neuroendocrine Effects On Endothelial Function and Muscle Glmentioning
confidence: 84%
“…30 Endothelial dysfunction is associated with cardiac autonomic dysfunction and increased HRV. 31,32 Moreover, we have recently reported that the HOMA index and the myocardial uptake of 123 I-MIBG at the delayed phase were independent predictors of adiponectin concentration. 7 In fact, in a recent report demonstrating the association between DR, insulin resistance and adiponectin, the authors stressed the central role of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%